HABS-BLOCKS© Inhibited Microcystis and Planktothrix and Reduced Microcystin Concentrations in a Lake Water Mesocosm Study - Cameron Gastaldo; Stephen Vesper (Microorganisms)
Toxins produced by cyanobacteria are a threat to drinking water and the aquatic ecosystem. Previously, we reported that adding glucose to lake water could reduce cyanobacterial populations. To target the glucose to the euphotic zone, floating HABS-BLOCKS© infused with glucose were created. On 12 June 2024, 24 L of bloom lake water was collected, and then 6 L was aliquoted into each of four 7 L mesocosms. Two HABS-BLOCKS© were added to each of two replicate treatment mesocosms, while two “Dummy” HABS-BLOCKS© (same but without glucose) were added to each of two control mesocosms. Cyanobacteria cell densities and microcystin concentrations were measured weekly. Total nitrogen and phosphorus and other water quality variables including dissolved oxygen, specific conductivity, and turbidity were measured at the end of the six-week experiment. Initially, Microcystis was measured at 2.4 × 103 cells/mL and Planktothrix at 5.0 × 102 cells/mL. After 6 weeks, both the Microcystis and Planktothrix population were significantly lower in the treated mesocosms compared to the controls. The initial microcystin concentration averaged 10.4 µg/L. By the third week of the experiment, the microcystin concentration was about 70% lower in the treated mesocosms. Total nitrogen was also lower in the HABS-BLOCKS©-treated mesocosm, but the other water quality measures were similar between the control and treated mesocosms. HABS-BLOCKS© appeared to reduce cyanobacterial cell densities, lower toxin concentrations, and lower total nitrogen while not having negative impacts on other water quality measures. Although much remains to be learned, this technology may someday be useful in suppressing HABS.